Radiocarbon dating of Chinese Ancient Tea Trees. Issue 6 (29th October 2019) - Chen, Jia; Shen, Hongtao; Sasa, Kimikazu; Lan, Haihui; Matsunaka, Tetsuya; Matsumura, Masumi; Takahashi, Tsutomu; Hosoya, Seiji; He, Ming; He, Yun; Li, Zhaomei; Zhao, Zhenchi; et al.
ABSTRACT: The jungles of Linyun and Longlin Autonomous Prefecture, located in the heart of the southwestern Guangxi Zhuang Autonomous Region of China, are home to the oldest tea trees ( Camellia sinensis ) in the world. In the absence of regular annual rings, radiocarbon ( 14 C) dating is one of the most powerful tools that can assist in the determination of the ages and growth rates of these plants. In this work, cores were extracted from large ancient tea trees in a central Longlin rain forest; extraction of carbon was performed with an automated sample preparation system. The 14 C levels in the tree cores were measured using accelerator mass spectrometry (AMS) at the University of Tsukuba. These measurements indicated that contrary to conventional views, the ages of trees in these forests range up to ~700 years, and the growth rate of this species is notably slow, exhibiting a long-term radial growth rate of 0.039±0.006 cm/yr. It was demonstrated that 14 C analyses provide accurate determination of ages and growth rates for subtropical wild tea trees.